Energy and economic costs of YTO DF 15L and DONGFENG DF 151L power tillers in soil preparation - Quimís-Guerrido, Byron; Shkiliova, Liudmyla; Guerrero-Arboleda, Benito; Franco-Plaza , Felipe; Zambrano-Arteaga, Ramón (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The objective of this study was to determine the energy and economic cost of the YTO DF 15L and DONGFENG DF 151L mechanized agricultural sets (double pass of rotovator) in the work of preparation of sandy-clay and loamy-clay soils, respectively. The methodology for determining total energy costs (MJ.h-1) and per worked area (MJ.ha-1) was used; likewise, Cuban Standard NC 34-38:2003 allowed the calculation of total economic costs (USD.h-1) and per worked area (USD.ha-1). The main findings showed that the total energy cost (EST) reached values of 78.50 and 75.30 MJ. h-1, with the energy sequestered by fuel (ESc) indicator prevailing with a share of 55 and 58.4%, in the EST structure, the energy costs per worked area EST (ha) registered 1.574,00 and 1.883,00 MJ.ha-1. On the other hand, the direct operating cost (Gd), reported 5.31 and 5.68 USD.h-1, with the cost per salary (Gs), the indicator that predominated with 68.and 70.4% in the distribution of Gd, and the cost per worked area (Gex), presented figures of 106.20 and 142.00 USD.ha-1, for the YTO DF 15L and DONGFENG DF 151L sets, respectively. The YTO DF 15L power tiller, with rotovator, distinguished itself as the agricultural  set with the lowest EST (ha) and Gex, by 16 and 25%, respectively, in the agricultural operation provided.